THE CONCEPT OF EARLY CHILDHOOD EDUCATION FROM THE PERSPECTIVE OF THE HADITH OF THE PROPHET MUHAMMAD SAW - Khairul Basruroh; Romlah Abubakar Askar; Abdul Ghofur (PT. Jurnal Center Indonesia Publisher, 2025)
This article discusses the importance of Early Childhood Education (PAUD) from the perspective of the Hadith of the Prophet Muhammad SAW. PAUD does not only focus on cognitive aspects, but also on moral education, aqidah, and worship. Through the habituation of Islamic values, good examples from parents, and positive communication, holistic education can be achieved. The type of research used in this study is library research with a qualitative approach. The data used in this study are secondary data obtained from various sources such as journals, books, official reports, and other credible and relevant documents. By integrating formal and informal education approaches, it is hoped that future generations can grow into individuals with noble morals and faith. The conclusion of this article emphasizes that the role of parents as primary educators is very important in shaping children's character in accordance with Islamic teachings. One way to create the instillation of religious and moral values ​​from an early age is to provide learning in the form of hadiths given to early childhood through a learning method in early childhood education institutions.